Nickel cluster catalyst supported on nanocarbon material, preparation method and application thereof

CN117772203BActive Publication Date: 2026-10-27INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311740909.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2026-10-27
Estimated Expiration
2043-12-18

AI Technical Summary

Technical Problem

该催化剂贵金属原子利用率低,乙烯选择性较低,同时副产物绿油生成量高,且随着贵金属价格的逐年攀升,催化剂成本显著增加

Benefits of technology

[0022]1、本发明首次采用纳米金刚石/石墨烯复合材料负载镍作为乙炔选择性加氢反应催化剂。该催化剂选用非贵金属镍为活性材料,纳米碳为载体,具有材料来源广泛、成本低、金属原子利用率高、环境友好、制造工艺成熟等优点,是贵金属催化剂的经济高效替代品,大大降低催化剂成本,极具工业化应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004613038320000011
    Figure HDA0004613038320000011
  • Figure HDA0004613038320000012
    Figure HDA0004613038320000012
  • Figure HDA0004613038320000021
    Figure HDA0004613038320000021
Patent Text Reader

Abstract

The application discloses a kind of nano carbon material supported nickel cluster catalyst and its preparation method and application, belong to the technical field of catalyst for selective hydrogenation of acetylene.The nano carbon material supported nickel cluster catalyst is used to hydrogenate acetylene to generate ethylene in mixed raw material gas, and the use temperature of the catalyst is 70 DEG C-200 DEG C;By dispersing nickel in the form of sub-nanometer cluster on nano carbon material, compared with traditional hydrogenation nickel catalyst and commercial palladium catalyst, the nano carbon material supported nickel cluster catalyst of the application can effectively catalyze the conversion of acetylene to ethylene, and the selectivity of acetylene hydrogenation is good, and the use of non-noble metal instead of noble metal greatly reduces the cost of catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalysts for acetylene hydrogenation reaction, specifically to a nickel cluster catalyst supported on nano-carbon materials, its preparation method, and its application. Background Technology

[0002] Ethylene (C2H4) is a fundamental chemical raw material for the synthesis of plastics, fibers, rubber, and other chemicals, and has significant industrial application value. However, the ethylene feed gas obtained from naphtha thermal cracking usually contains a small amount of acetylene impurities. The presence of acetylene impurities not only poisons the catalysts in downstream polymerization reactions but also leads to a decline in the quality of polymer products. Therefore, the selective hydrogenation of the small amount of acetylene impurities in the ethylene feed gas to ethylene is of great importance in the ethylene industrial production process.

[0003] The most widely used traditional selective hydrogenation catalyst for acetylene in the ethylene industry is the alumina-supported palladium-silver catalyst. This catalyst uses alumina as the support, palladium as the active metal component, and silver as a structural aid. However, this catalyst suffers from low atom utilization of the precious metal, low ethylene selectivity, high production of the byproduct green oil, and a significant increase in catalyst cost due to the rising price of precious metals.

[0004] Therefore, this invention attempts to utilize nano-carbon materials as a carrier and inexpensive non-precious metal nickel as the active metal component to develop a new low-cost, highly active, and highly selective catalyst suitable for the selective hydrogenation reaction of acetylene. Summary of the Invention

[0005] The purpose of this invention is to provide a nano-carbon supported nickel cluster catalyst, its preparation method and application. The prepared nano-carbon supported nickel cluster catalyst realizes non-noble metal acetylene hydrogenation catalysis and has high selectivity in the acetylene hydrogenation reaction.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows:

[0007] A nanocarbon-supported nickel cluster catalyst for the selective hydrogenation of acetylene is disclosed. The catalyst uses nickel as the active material and a nanodiamond / graphene composite material as the support, with nickel dispersed and anchored on the support surface in the form of atomic clusters. The nickel loading in the catalyst is 0.1–1 wt.% of the support mass, preferably 0.5–0.75 wt.%. The cluster size distribution is 0.2–1 nm, preferably 0.4–0.8 nm.

[0008] The nano-carbon carrier has a core-shell structure and is obtained by high-temperature calcination of nanodiamond powder. The nanodiamond (ND) has a particle size of 5-7 nm. After high-temperature calcination (calcination treatment at 900-1100℃ for 4-6 hours), a phase transformation occurs on the surface of the nanodiamond, forming an epitaxially grown graphene layer with carbon defects on the surface of the nanodiamond. The number of graphene layers is about 2-4, and the internal structure of the graphene layer is still maintained, forming a nanodiamond / graphene composite material (ND@G) with nanodiamond as the core and graphene as the shell.

[0009] Furthermore, nickel can be loaded onto a nano-carbon support by deposition or strong electrostatic adsorption, and the structure of the nickel species loaded on the support can be controlled by changing the nickel loading or material reduction treatment, thereby preparing a nano-carbon supported nickel cluster catalyst.

[0010] Specifically, the steps include the following:

[0011] (1) Nanodiamond / graphene composite material, i.e. nano carbon material carrier, is obtained by calcining nanodiamond powder at high temperature in an inert atmosphere.

[0012] (2) Nickel species are deposited onto the nano-carbon material support by deposition precipitation method or strong electrostatic adsorption method to obtain nano-carbon supported nickel catalyst precursor.

[0013] (3) The nano-carbon supported nickel catalyst precursor is placed in a quartz tube and reduced in a hydrogen atmosphere (high-purity hydrogen or hydrogen-helium mixture) to obtain the nano-carbon supported nickel cluster catalyst.

[0014] The preferred experimental scheme is as follows:

[0015] In step (1) above, the specific process of the high-temperature treatment method is as follows: 1.5g of nanodiamond powder (particle size of 5-7nm) is placed in a high-temperature tube furnace, heated to 1100℃ in an inert gas Ar atmosphere and kept at that temperature for 4h, with a gas flow rate of 100mL / min. After cooling to room temperature, it is taken out to obtain nanodiamond / graphene material.

[0016] In step (2) above, the deposition precipitation method preparation process is as follows: 30 mL of ultrapure water is added to a 100 mL round-bottom flask, 200 mg of nano-carbon support is added, and the mixture is ultrasonically dispersed to obtain a nano-carbon support dispersion. The amount of nickel chloride precursor is calculated according to the nickel loading in the catalyst being 0.5 wt.%, and then 1 mL of the prepared nickel chloride precursor solution (concentration of 0.017 mol / L) is added to the obtained nano-carbon support dispersion. The mixture is placed in a 90 °C oil bath, and 0.25 mol / L sodium carbonate solution is added dropwise to the solution under stirring to adjust the pH value to 9-9.5. Finally, the mixture is kept at 90 °C and stirred for 1 h, then cooled to room temperature. After filtration and washing, the sample is placed in a 60 °C vacuum drying oven and kept at 12 h. After cooling, the sample is taken out to obtain the nano-carbon supported nickel catalyst precursor.

[0017] The reduction process described in step (3) above is as follows: 60 mg of nano-carbon supported nickel catalyst precursor is placed in a quartz reaction tube, a hydrogen-helium mixture (hydrogen gas integral of 10 vol.%) is introduced, the flow rate is 60 mL / min, and the reduction is carried out at 300 °C for 1 h to obtain nano-carbon supported nickel cluster catalyst.

[0018] The nano-carbon supported nickel cluster catalyst was used as a catalyst for the hydrogenation reaction of acetylene, catalyzing the selective hydrogenation of acetylene to ethylene in a mixed feed gas.

[0019] In the acetylene hydrogenation reaction, the catalyst is used at a temperature of 70–200°C (preferably 130–200°C); the preferred gas contents in the mixed feed gas are: acetylene 1 vol.%, hydrogen 10 vol.%, ethylene 20 vol.%, and helium as the balance gas; the preferred space velocity is 20,000 mL·g. -1 ·h -1 .

[0020] When used in the hydrogenation of acetylene, this catalyst achieves an acetylene conversion rate of 0.1–100% and an ethylene selectivity of 80–100%.

[0021] The advantages of this invention are as follows:

[0022] 1. This invention is the first to use nickel supported on a nanodiamond / graphene composite material as a catalyst for the selective hydrogenation of acetylene. This catalyst uses non-precious metal nickel as the active material and nano-carbon as the support, offering advantages such as wide availability of materials, low cost, high metal atom utilization, environmental friendliness, and mature manufacturing processes. It is an economical and efficient alternative to precious metal catalysts, significantly reducing catalyst costs and showing great promise for industrial application.

[0023] 2. This invention employs a nano-carbon supported nickel cluster catalyst as the catalyst for the acetylene hydrogenation reaction. This catalyst exhibits excellent acetylene hydrogenation activity during the reaction, with a high ethylene yield, successfully achieving efficient acetylene hydrogenation using non-precious metals. At 190℃, the acetylene conversion rate is 100%, and the ethylene selectivity is 91%.

[0024] 3. The catalyst used in this invention has a mature production process, a simple preparation method, and can be produced on a large scale.

[0025] 4. Nanocarbon materials can be used as catalyst supports to recover metals from spent catalysts through combustion. Attached Figure Description

[0026] Figure 1 HRTEM image of ND@G nanodiamond / graphene composite material prepared in Example 1;

[0027] Figure 2 To prepare the Ni obtained in Example 2 n HAADF-STEM image of / ND@G;

[0028] Figure 3 For Ni p HAADF-STEM image of / ND@G;

[0029] Figure 4 HAADF-STEM image of Ni1 / ND@G;

[0030] Figure 5 The graph shows the changes in acetylene conversion and ethylene selectivity as a function of temperature for Examples 1, 4, Comparative Examples 1 and 2. Detailed Implementation

[0031] The present invention will be described in detail below with reference to the embodiments.

[0032] Preparation Example 1

[0033] Preparation Example 1 illustrates the preparation process of carbon nanofiber supports:

[0034] 1.5g of nanodiamond powder (particle size 5-7nm) was placed in a high-temperature tube furnace, heated to 1100℃ in an inert Ar atmosphere and held for 4h with a gas flow rate of 100mL / min. After cooling to room temperature, the nanodiamond / graphene composite material was obtained, denoted as ND@G.

[0035] like Figure 1As shown, high-resolution transmission electron microscopy (HRTEM) images of ND@G clearly reveal the diamond (111) lattice fringes in its core, indicating that the core of ND@G retains its diamond structure after calcination. Furthermore, epitaxially grown graphene layers with carbon defects are observed on the surface of ND@G along the nanodiamond surface, with an interlayer spacing of 0.34 nm and approximately 2–4 graphene layers on the nanodiamond surface. This demonstrates the core-shell structure of the composite material, with nanodiamond as the core and graphene as the shell. Raman characterization further confirms that ND@G possesses diamond sp. 3 Hybrid and defective graphene sp 2 Hybrid composite structure, I D / I G The value is 0.7.

[0036] Preparation Example 2

[0037] Preparation Example 2 is a precursor of nano-carbon supported nickel catalyst prepared by deposition precipitation method. The preparation process is as follows: 200 mg of nano-carbon support powder obtained in Preparation Example 1 was mixed with 30 mL of ultrapure water in a 100 mL round-bottom flask and ultrasonically dispersed evenly; then 1 mL of nickel chloride precursor solution with a concentration of 0.017 mol / L (theoretical loading is 0.5 wt.% of the support) was added to the nano-carbon support dispersion; the flask was placed in a 90 °C oil bath, and 0.25 mol / L sodium carbonate solution was added dropwise under stirring to adjust the pH value to 9.3. Finally, the mixture was kept at 90 °C and stirred for 1 h, then cooled to room temperature. After filtration and washing with ultrapure water, the sample was placed in a 60 °C vacuum drying oven and kept at 12 h. After cooling, the sample was taken out to obtain the nano-carbon supported nickel catalyst precursor.

[0038] Preparation Example 3

[0039] Preparation Example 3 is a precursor of nano-carbon supported nickel catalyst prepared by strong electrostatic adsorption method. The preparation process is as follows: 200 μL of nickel nitrate solution (concentration of 0.22 mol / L) is mixed with 20 mL of ammonia solution with a concentration of 5 mol / L. 500 mg of nano-carbon support powder prepared in Preparation Example 1 is added to the mixture. The mixture is stirred at room temperature for 2 hours. After filtration and washing with ultrapure water, the sample is placed in a vacuum drying oven at 60 °C and kept at that temperature for 12 hours. After cooling, the sample is taken out to obtain the nano-carbon supported nickel catalyst precursor.

[0040] Example 1

[0041] 60 mg of the nano-carbon supported nickel catalyst precursor prepared in Example 2 was placed in a quartz tube. The quartz tube was then placed in a fixed-bed reactor, and a hydrogen-helium mixture (hydrogen integral of 10 vol.%) was introduced at a flow rate of 60 mL / min. The mixture was then subjected to in-situ reduction at 300 °C for 1 h to obtain the nano-carbon supported nickel cluster catalyst, denoted as Ni. n / ND@G. Ni can be observed using aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). n In / ND@G, nickel is mainly dispersed on the carrier surface in the form of small atomic clusters. It is anchored to the carrier surface by bonding with carbon atoms on the graphene layer. The carrier maintains a core-shell structure with nanodiamond as the core and graphene as the shell. The nickel cluster size is distributed in the range of 0.4–0.6 nm (e.g., ...). Figure 2 (as shown);

[0042] A mixed feed gas (1% acetylene, 10% hydrogen, 20% ethylene, with helium as the balance gas, the percentages being volume percentages) is introduced at a space velocity of 20000 mL·g. -1 ·h -1 The temperature was increased from room temperature, and samples were taken twice every 10°C from 50°C to 200°C. The heating rate was 2°C / min, and the holding time at each temperature was 40min. The reaction products were detected by online gas chromatography.

[0043] The acetylene hydrogenation test results showed that the acetylene conversion rate was 100% and the ethylene selectivity was 91% at 190℃.

[0044] Example 2

[0045] The process and conditions are the same as in Example 1, except that 60 mg Ni is used. n / ND@G at an air velocity of 12000 mL·g -1 ·h -1 Acetylene hydrogenation performance was tested, using the same catalytic materials and testing procedures as in Example 1. The acetylene hydrogenation test results showed that acetylene was completely converted at 180°C, with an ethylene selectivity of 86%.

[0046] Example 3

[0047] The process and conditions are the same as in Example 1, except that 60 mg Ni is used. n / ND@G at an air velocity of 15000 mL·g -1 ·h -1 Acetylene hydrogenation performance was tested, using the same catalytic materials and testing procedures as in Example 1. The acetylene hydrogenation test results showed that acetylene was completely converted at 190°C, with an ethylene selectivity of 90%.

[0048] Example 4

[0049] 60 mg of the nano-carbon supported nickel catalyst precursor prepared in Example 3 was placed in a quartz tube. The quartz tube was then placed in a fixed-bed reactor, and a hydrogen-helium mixed gas (hydrogen integral of 10 vol.%) was introduced at a flow rate of 60 mL / min. The mixture was then subjected to in-situ reduction at 300 °C for 1 h to obtain the nano-carbon supported nickel cluster catalyst, denoted as Ni.n / ND@G-SEA. Ni can be observed using spherical aberration electron microscopy. n In / ND@G-SEA, nickel is mainly dispersed on the support surface in the form of atomic clusters, which are anchored to the support surface by bonding with carbon atoms on the graphene layer surface. The cluster size is distributed in the range of 0.6 to 0.8 nm.

[0050] At an air velocity of 20000 mL·g -1 ·h -1 Acetylene hydrogenation performance was tested under the same procedures and conditions as in Example 1. The acetylene hydrogenation test results showed that at 200°C, the acetylene conversion rate was 100%, and the ethylene selectivity reached 88%.

[0051] Example 5

[0052] The process and conditions are the same as in Example 1, except that this example uses Ni obtained at an in-situ reduction temperature of 250°C. n / ND@G catalyst, observed using aberration-corrected electron microscopy in Ni n In / ND@G, the nickel cluster size distribution ranges from 0.2 to 0.4 nm. Acetylene hydrogenation tests show that at 200 °C, the acetylene conversion is 85%, and the ethylene selectivity reaches 100%.

[0053] Example 6

[0054] The process and conditions are the same as in Example 1, except that this example uses Ni obtained at an in-situ reduction temperature of 350°C. n / ND@G catalyst, aberration-corrected electron microscopy can be used to observe the presence of Ni. n In / ND@G, the nickel cluster size distribution ranges from 0.8 to 1 nm. Acetylene hydrogenation tests show that at 190 °C, the acetylene conversion is 100%, and the ethylene selectivity reaches 82%.

[0055] Comparative Example 1

[0056] The process and conditions are the same as in Example 1, except that this comparative example uses Ni obtained at an in-situ reduction temperature of 400°C. p / ND@G catalyst, Ni can be observed using aberration-corrected electron microscopy. p In / ND@G, Ni (111) lattice fringes are present with a lattice spacing of 0.203 nm. In this catalyst, Ni is supported in particulate form on the surface of a nano-carbon support, with a particle size distribution of 3–7 nm (e.g., ...). Figure 3 (As shown). The acetylene hydrogenation test results showed that acetylene was completely converted at 150℃, and the ethylene selectivity was -42%. This is because the presence of Ni particles led to excessively high hydrogenation activity and severe over-hydrogenation, resulting in poor ethylene selectivity of the nickel particle catalyst.

[0057] Comparative Example 2

[0058] The process and conditions were the same as in Example 1, except that this comparative example used Ni1 / ND@G obtained at an in-situ reduction temperature of 200℃ as a catalyst. Aberration-corrected electron microscopy revealed that nickel in Ni1 / ND@G mainly existed in single-atom form, with a size distribution of 0.1–0.2 nm (e.g., ...). Figure 4 (As shown). The acetylene hydrogenation test results showed that the conversion rate of acetylene at 200℃ was 0.5%, and the ethylene selectivity was 100%. This indicates that single-atom nickel has lower hydrogenation activity compared to nickel clusters.

[0059] Comparative Example 3

[0060] The acetylene hydrogenation performance test process and conditions were the same as in Example 1, except that the comparative example used the ND@G support prepared in Preparation Example 1 as the catalyst. The acetylene hydrogenation test results showed that the conversion rate of acetylene was 0 at 200°C.

[0061] Comparative Example 4

[0062] The process and conditions were the same as in Example 1, except that this comparative example used a 0.5 wt.% Ni / G catalyst prepared on a graphene support (nickel loading was 0.5 wt.% of the support), and the catalyst precursor preparation method (process and conditions) was the same as in Example 2. Aberration-corrected electron microscopy revealed a low degree of Ni particle dispersion on the graphene support, with a size distribution of 2–3 nm. Acetylene hydrogenation tests showed that the acetylene conversion was 100% at 170 °C, and the ethylene selectivity reached 35%.

[0063] Comparative Example 5

[0064] The process and conditions were the same as in Example 1, except that this comparative example used 0.5 wt.% Ni / OLC catalyst (nickel loading was 0.5 wt.% of the support) prepared from onion carbon (OLC) obtained by calcining nanodiamond at 1500℃ for 4 h in an Ar atmosphere (gas flow rate of 100 mL / min). The catalyst precursor preparation method (process and conditions) was the same as in Example 2. TEM images of the OLC showed that when the calcination temperature was 1500℃, the diamond phase of the nanodiamond was completely transformed into the graphite phase, and the outer sp... 2 The number of graphitic carbon layers increased significantly, and the material became highly graphitized, forming an onion-like carbon structure. Aberration-corrected electron microscopy revealed that nickel species existed as small particles in 0.5 wt.% Ni / OLC, with a size distribution ranging from 1.5 to 1.7 nm. Acetylene hydrogenation tests showed that the acetylene conversion was 100% at 180 °C, and the ethylene selectivity reached 40%.

[0065] Comparative Example 6

[0066] The process and conditions were the same as in Example 1, except that in this comparative example, alumina powder (particle size 10-15 nm) was used as a support to prepare a Ni / Al2O3 catalyst with a loading of 0.5 wt.% (nickel loading was 0.5 wt.% of the support). The catalyst precursor preparation method (process and conditions) was the same as in Example 2. Acetylene hydrogenation tests showed that the conversion rate of acetylene at 200 °C was 0.

[0067] Comparative Example 7

[0068] The process and conditions were the same as in Example 1, except that in this comparative example, nano-titanium dioxide (particle size 5-10 nm) was used as a support to prepare a Ni / TiO2 catalyst with a loading of 0.5 wt.% (nickel loading was 0.5 wt.% of the support). The catalyst precursor preparation method (process and conditions) was the same as in Example 2. Acetylene hydrogenation tests showed that the conversion rate of acetylene at 200 °C was 3.3%.

[0069] Comparative Example 8

[0070] The process and conditions were the same as in Example 1, except that in this comparative example, nano-silica (particle size 20 nm) was used as a support to prepare a Ni / SiO2 catalyst with a loading of 0.5 wt.% (nickel loading was 0.5 wt.% of the support). The catalyst precursor preparation method (process and conditions) was the same as in Example 2. Acetylene hydrogenation tests showed that the conversion rate of acetylene at 200 °C was 1.2%.

[0071] The above examples and comparative examples illustrate that the nano-carbon supported nickel cluster catalyst prepared by the method of the present invention can achieve high acetylene conversion and ethylene selectivity in the acetylene hydrogenation reaction.

[0072] Comprehensive characterization and experimental results show that this invention successfully constructs non-noble metal nickel active sites on a nanodiamond / graphene support. The metal size effect significantly influences the acetylene hydrogenation performance. The nanocarbon-supported nickel cluster catalyst described in this invention achieves 100% acetylene conversion and 91% ethylene selectivity in the acetylene hydrogenation reaction at 190℃, simultaneously achieving high acetylene conversion and high ethylene selectivity. Moreover, the catalyst has a mature synthesis method, a convenient and easy-to-implement modification process, is easy to recycle and environmentally friendly, and has low catalyst cost.

[0073] The above are preferred embodiments of the present invention, but the scope of protection of the present invention is not limited to the above embodiments. Variations and advantages that can be conceived by those skilled in the art without departing from the spirit and scope of the inventive concept are also included in the present invention.

Claims

1. The application of a nickel cluster catalyst supported on nano-carbon material as a catalyst for the hydrogenation reaction of acetylene, characterized in that: The nickel cluster catalyst supported on the nano-carbon material was used as a catalyst for the selective hydrogenation of acetylene to produce ethylene. The catalyst uses non-precious metal nickel as the active material and nano-carbon material as the support. Nickel is dispersed on the nano-carbon material support in the form of clusters with a cluster size distribution of 0.2~1 nm. The nickel loading was 0.5~0.75 wt.% of the carrier mass; The aforementioned nano-carbon material carrier is a nanodiamond / graphene composite material; this material has a core-shell structure, with nanodiamond as the core and graphene as the shell; the material is obtained by high-temperature treatment of nanodiamond, with a nanodiamond particle size of 5~7 nm; after calcination at 900~1100 ℃ for 4~6 h, the carbon atoms on the surface of the nanodiamond are reconstructed, forming a graphene layer with carbon defects that grows epitaxially along the surface of the nanodiamond, while its core still maintains the diamond structure; the number of graphene layers on its surface is 2~4. Nickel is loaded onto the surface of a nano-carbon material support by deposition or strong electrostatic adsorption to obtain a nano-carbon supported nickel catalyst precursor, which is then reduced to obtain the nano-carbon material supported nickel cluster catalyst. In the acetylene hydrogenation reaction, the catalyst is used at a temperature of 70–200 °C; the mixed feed gas contains: acetylene 0.5–1 vol.%, hydrogen 5–10 vol.%, ethylene 10–20 vol.%, and helium as the balance gas; the space velocity is 6000–60000 mL·g. -1 ·h -1 .

2. The application of the nano-carbon material-supported nickel cluster catalyst according to claim 1 as a catalyst for the hydrogenation reaction of acetylene, characterized in that: The nano-carbon material carrier is obtained by high-temperature treatment of nano-diamond, including the following steps: 1.2~1.5 g of nano-diamond powder with a particle size of 5~7 nm is placed in a high-temperature tube furnace and calcined at 900~1100 ℃ for 4~6 h in an Ar atmosphere of 80~100 mL / min. After cooling to room temperature, it is taken out to obtain the nano-diamond / graphene composite material.

3. The application of the nano-carbon material-supported nickel cluster catalyst according to claim 1 as a catalyst for the hydrogenation reaction of acetylene, characterized in that: The preparation process of the deposition precipitation method is as follows: 200-500 mg of nano-carbon material carrier powder is mixed with 30-40 mL of water in a container and dispersed evenly. Then, a nickel chloride solution is added. The mass ratio of the nano-carbon material carrier powder to the nickel in the nickel chloride solution is 100:0.1-1, and the concentration of the nickel chloride solution is 0.004-0.04 mol / L. The suspension is stirred at 90-100 °C, and sodium carbonate solution is added dropwise to adjust the pH value to 9-9.

5. The concentration of the sodium carbonate solution is 0.25-0.5 mol / L. The mixture is kept at this temperature and stirred for 1-2 h. Then, it is cooled to room temperature. After filtration and washing, the sample is placed in a vacuum drying oven at 60-80 °C and kept at this temperature for 12-18 h. After cooling, it is taken out to obtain the nano-carbon supported nickel catalyst precursor. Alternatively, the preparation process of the strong electrostatic adsorption method is as follows: Nickel nitrate solution and 10-20 mL of ammonia solution (concentration 5-5.6 mol / L) are mixed in a container. Then, 200-500 mg of nano-carbon material carrier powder is added, wherein the mass ratio of the nano-carbon material carrier powder to nickel in the nickel nitrate solution is 100:0.1-1, and the concentration of the nickel nitrate solution is 0.03-0.9 mol / L. The mixture is stirred at room temperature for 1-2 h, filtered, washed, and then placed in a vacuum drying oven at 60-80 ℃ for 12-18 h. After cooling, the sample is removed to obtain the nano-carbon supported nickel catalyst precursor.

4. The application of the nano-carbon material-supported nickel cluster catalyst according to claim 1 as a catalyst for the hydrogenation reaction of acetylene, characterized in that: The reduction process involves placing 50-100 mg of the nano-carbon supported nickel catalyst precursor in a quartz tube and reducing it in a high-purity hydrogen or hydrogen-helium mixture to obtain the nano-carbon supported nickel cluster catalyst. The hydrogen gas fraction in the hydrogen-containing atmosphere is 10 vol.% to 100 vol.%, the flow rate of the mixed gas is 20-100 mL / min, the reduction temperature is 240-360 ℃, and the reduction time is 0.5-2 h.

5. The application of the nickel cluster catalyst supported on nano-carbon material according to claim 1 as a catalyst for the hydrogenation reaction of acetylene, characterized in that: In the acetylene hydrogenation reaction, the acetylene conversion rate is 0.1-100%, and the ethylene selectivity is 80-100%.

Citation Information

Patent Citations

  • Nano-carbon loaded atomic-scale dispersion copper-based catalyst, and preparation method and application thereof

    CN109806867A